Ferroptosis and its emerging role in esophageal cancer - Maimaitizunong, Rezeye; Wang, Kai; Li, Hui (Frontiers in Molecular Biosciences, 2022)
The occurrence and development of tumor involve a series of life activities of cells, among which cell death has always been a crucial part in the research of tumor mechanism and treatment methods. Ferroptosis is a non-apoptotic form of cell death, which is characterized by lipid peroxidation accumulation and further cell membrane rupture caused by excessive production of intracellular oxygen free radicals dependent on iron ions. Esophageal cancer is one of the common digestive tract tumors. Patients in the early stage are mainly treated with surgery, and the curative effect is awe-inspiring. However, surgery is far from enough for terminal patients, and it is the best choice to combine radiotherapy and chemotherapy before the operation or during the perioperative period. Although the treatment plan for patients with advanced esophageal cancer is constantly being optimized, we are disappointed at the still meagre five-year survival rate of patients and the poor quality of life. A series of complex problems, such as increased chemotherapy drug resistance and decreased radiotherapy sensitivity of esophageal cancer cells, are waiting for us to tackle. Perhaps ferroptosis can provide practical and feasible solutions and bring new hope to patients with advanced esophageal cancer. Duo to ferroptosis is related to iron metabolism, lipid metabolism and glutamic acid metabolism, the metabolic participant proteins and signal pathways are essential for cancer therapy by ferroptosis. This review first introduced the main regulatory mechanisms of ferroptosis. It then summarized the current research status of ferroptosis in esophageal cancer, expecting to provide ideas for the research related to ferroptosis in esophageal cancer.